Framework Design for the Retrieval of Instant Messaging in Social Media as Electronic Evidence - Linda Rosselina; Yohan Suryanto; Tofan Hermawan; Fahdiaz Alief (Proceeding of the Electrical Engineering Computer Science and Informatics, 2020)
The rapid growth of social media features not only brings many advantages but also causes problems. Mainly related to digital evidence when cybercrime occurs. One of the social media features that are currently popular is the unsend message feature in instant messaging applications such as Instagram, Whatsapp, Facebook Messenger, Skype, Viber, and Telegram. In the case of cybercrime, the perpetrator can delete the messages and erase digital evidence, making it difficult to trace. Those artifact messages might be useful for law enforcement or forensic investigators to be used as digital evidence in court. Therefore, an effective and efficient framework is needed in the mobile forensic investigation process to guarantee the integrity of the data obtained. This paper will discuss the review of several international standards on mobile forensics, namely NIST SP 800-101, ISO/ IEC, and SWGDE. This paper also proposes a framework design to retrieve unsend data artifacts on social media according to official and widely used international mobile forensic standards.